Attitudes of Iraqi Medical Schools Teachers and Students towards the Textbook: New Headway Beginner Plus - Basheer, Nibras A. (Al-Adab Journal, 2019)
Discovering the attitudes of instructors and learners towards a textbook is an essential step for a proper evaluation of that book and the success of the teaching process. The current study was conducted especially for students of medical colleges in Baghdad to be a model and a path to apply to other medical schools. It is to figure out the views and attitudes of teachers and learners about the curriculum of the series, "New Headway Beginner Plus". Two questionnaires and an interview have been made. The result of the study showed that the teachers and learners consider the textbook level is below the level of Iraqi medical students and it does not meet the students' needs in learning and their occupational future. In fact, all med-students came from secondary schools without ESP background by which they can use medical language in context to communicate and convey meaning considering the doctor-patient or doctor-student relationships. Instructors (Doctors) and students need medical terms with general language to cope with the science of morphology depending on Greek or Latin origins of words to form new medical terms. All kinds of learning medical English language terms are very useful in communication and their future careers